Prevalencia de babesiosis canina en la ciudad de Machala - Astudillo León, Jorge Azael (2010)
The investigation work was carried out with the collaboration of the Veterinary Clinics in the city of Machala, El Oro Province, from February to June of 2009. The objectives of the in-vestigation were: 1. To determine the prevalence of Babesia canis in dogs in the city of Machala. 2. To determine the prevalence according to the breed, age and sex. The number of gathered samples was of 200 taken of dogs that presented symptoms of the disease. To take the blood samples the hair was cut disinfected the area with alcohol or iodine, a tourniquet was made to obtain a better visibility of the radial vein and the blood was extracted using 3 cm syringes in which previously were placed two drops of anticoagulant (EDTA). Then, to carry out the smear it was allowed to dry spontaneously to the air, it was fixed with methyl alcohol for 20 minutes, the alcohol was discarded and allowed to dry off to the atmosphere, then, and the coloring was placed. The coloring was set to act for 20 minutes, later it dried off and washed and then it was observed to the microscope with immersion lens. The hemoparasite was identified to the microscope in the cytoplasm of the red globule, which presented a pear shape. In the investigation it was determined, The presence of Babesia canis in dogs in the city of Machala which result was of 42,5 %. The prevalence of Babesia canis was bigger in male dogs represented by 23,5 % and for the females it was of 19,5 %. The Babesia canis is present in all ages. The Babesia canis is present in all breeds.